A Multiobjective Pricing Model in Omnichannel Retailing With Emphasis on State Interventions - Mehrdad Bahremand; Roya Soltani; Rasoul Karimi (IEEE Access, 2022)
In recent years, pricing and coordination among manufacturers, suppliers, and retailers in multi-level supply chains (SCs) have attracted researchers’ attention. Product pricing can be considered one of the main aspects in the management of SCs. The lack of a proper pricing strategy leads to low sales numbers, customers, market share, and profit. The present study aimed at modeling optimal pricing in a multi-level SC, including suppliers, retailers, and customers, where customers place demand for different products, the price of which is a function of the set of prices defined by suppliers from different distribution channels, presented as a nonlinear scheduling problem. Minimum and maximum prices and demands for the product are defined using this model. However, according to different discount scenarios in distribution channels set by suppliers, customers’ demand is determined in a minimum-maximum range. The proposed model sets pricing and ordering, determines delivery centers, and chooses routes and vehicles to maximize the SC profits. The model was devised using the combined method of simulated annealing and red deer with approximate data to sell mobile products and accessories. The results indicated that customers tended to go for online shopping more than in-person shopping. Increasing the product cost reduces demand for the product and increases demand for a competitive product. In general, the decrease in demand for a product is higher than the growth of demand for a competitive product, i.e., the decrease in demand reduces the need for shelves.